2009
DOI: 10.1007/s00404-009-1072-6
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6, interleukin-10 and interleukin-12 in vaginal fluid from women with bacterial vaginosis

Abstract: The marked alteration in the vaginal bacterial flora that is characteristic of BV does not result in enhancement or inhibition of the vaginal levels of IL-6, IL-10 and IL-12. Mechanisms to explain this striking lack of immune system variation remain to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
3
8
0
1
Order By: Relevance
“…Researchers have reported that an increase in IL-12 was present in women with increased vaginal pH, a characteristic of women with BV compared to health women [16, 29], and we also found statistically significant values. In our study, we found that increased IL-12 was associated with BV patients co-infected with HPV strains ( P = 0.039), but not those who have coinfection with high-risk HPV strains ( P = 0.256).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Researchers have reported that an increase in IL-12 was present in women with increased vaginal pH, a characteristic of women with BV compared to health women [16, 29], and we also found statistically significant values. In our study, we found that increased IL-12 was associated with BV patients co-infected with HPV strains ( P = 0.039), but not those who have coinfection with high-risk HPV strains ( P = 0.256).…”
Section: Discussionsupporting
confidence: 81%
“…Many of these cytokines, known as interleukins (IL), are produced by certain populations of leukocytes residing in the bloodstream, including monocytes, neutrophils, or eosinophils [12, 15]. The pattern of immune response can be divided into Th1, Th2, and Treg, these three patterns are best known; however, others as the Th-17 have been described [16]. Increase in the levels of IL-10 from T lymphocytes in culture supports the hypothesis that the immunosuppression of Th2 cytokines may promote the development of cervical lesions [17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we provide the first quantitative evaluation of vaginal epithelial exfoliation in BV, demonstrating increased shedding of epithelial cells in both G. vaginalis infected mice and in clinical specimens from women with BV compared to mock-infected mice or women with normal flora respectively. This epithelial response is contrasted by an absence of inflammatory cell infiltrate, consistent with the lack of vaginal inflammation found in human BV throughout the literature [51][53]. The results from this murine model suggest that G. vaginalis alone is sufficient to yield BV phenotypes and provide further justification for considering G. vaginalis as a contributor to the causes and complications associated with BV.…”
Section: Introductionsupporting
confidence: 80%
“…It has been proposed that genital infection with GV and some species from the Mycoplamataceae family, such as UU, contribute to HPV persistence through the impairment of immune response pathways. Vaginal secretions from individuals infected with GV presented increased expression of IL10, which is associated with a reduced cytotoxic Th1 T‐cell response [Weissenbacher et al, ]. Few studies have reported the prevalence of Gardnerella vaginalis in the Mexican population.…”
Section: Discussionmentioning
confidence: 99%